Clustering of small and medium-sized enterprises as a strategy for their competitiveness - (:unkn) unknown (Portland State University, 2015)
Economies in the world are supporting small and medium-sized enterprises (SMEs) due to increasing unemployment rates. But increasing costs of inputs for production of goods and services are barriers to competitiveness and growth of SMEs. Clustering of SMEs is an appropriate strategy to overcome these limitations, since it enables to reduce costs of inputs through collaborative contracts with suppliers and gain competitive advantages in the marketplace. Although it is an appropriate strategy, clustering is a difficult process for SMEs. This paper explains competitive advantages of clustering of SMEs and describes a clustering process for procurement. Clustering makes it possible for SMEs to benefit from economies of scale and high quality levels available to large enterprises, and hence achieve sustainable competitiveness. Sustainable competitiveness of SMEs is the key to their growth and their investments in technology and R&D. © 2014 Portland International Conference on Management of Engineering and Technology.